PENELUSURAN POTENSI MIKROBA ENDOFIT DARI RIMPANG PAKU KEPALA TUPAI (Drynaria quercifolia J.Smith) SEBAGAI PENGHASIL SENYAWA ANTIBIOTIKA - Rusli Rusli; Dian Rahmaniar (Fakultas Farmasi UMI, 2013)
This research object to obtain abd determine the activity of antibiotics microbial isolates from endophyticpakukepalatupai (Drynariaquercifolia J. Smith) as a producer of antibiotic compounds. Methods research is using the method in a medium cast nutrient agar and potato dextrose agar with a dilution of 10-1 to 10-5. Result showed that there were 5 active isolates on thosetwo medium, identification of isolates bacterial and fungi. Then, the bacteria and fungi isolates purified by quadrant method on nutrient agar and potato dextrose agar medium were in mikroskopic. To produce antibiotic compound fermentation carried out by maltose yeast broth. The results of testing the activity of an antibiotic fermentation with agar diffusion method, results showed that the bacterial active against Bacillus subtilis, Pseudomonas aeruginosa, Streptococcus mutans, Escherichia coli and fungal isolates aktifagains candida albicans. Identification of endophyte microbe isolates carried out by gram staining. Result obtained showed that all isolates of the bacteria were negative Gram and coccus and bacil from.Key word : Antibiotic, Microbial Endophyte, Drynaria quercifolia J. Smith